2022
DOI: 10.3389/feduc.2022.1022295
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric analysis of the flipped classroom pedagogical model: Trends and strategic lines of study

Abstract: The Flipped Classroom (FC) emerged at the beginning of the 20th century as an alternative pedagogical model to the traditional classroom. It consists of inverting (flipping) some teaching-learning procedures, transferring some activities outside the classroom and reformulating the roles of the teacher and the student. The aim of this study is to identify the main existing trends and emerging strategic lines of research with respect to the FC pedagogical model. To this end, a bibliometric study was carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…The FC model can be encompassed within what we will call active methodologies, which are focused on the learning of the student ( Kane, 2007 ), provide more flexibility in their implementation, and which transform themselves into learning processes that are more independent from the physical space where they take place. Therefore, the methodological transformations performed by the professors to flip the classroom ( Namaziandost and Çakmak, 2020 ; Stöhr et al., 2020 ; del Arco et al., 2022 ) can be considered a prelude that will facilitate virtualization a posteriori.…”
Section: -Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FC model can be encompassed within what we will call active methodologies, which are focused on the learning of the student ( Kane, 2007 ), provide more flexibility in their implementation, and which transform themselves into learning processes that are more independent from the physical space where they take place. Therefore, the methodological transformations performed by the professors to flip the classroom ( Namaziandost and Çakmak, 2020 ; Stöhr et al., 2020 ; del Arco et al., 2022 ) can be considered a prelude that will facilitate virtualization a posteriori.…”
Section: -Discussionmentioning
confidence: 99%
“…The origin of this model is found in 2006, created by two teachers from Woodland Park High School (Colorado), Bergmann and Sams (2014) . Although the starting basis was to substitute an explanation in the classroom with a video, the concept has evolved towards a methodology that has shifted beyond this initial idea ( Llamazares, 2014 ; Flores, 2015 ; del Arco et al., 2022 ). It now promotes the diversification of resources and allows the teacher to make different decisions about the act of teaching and the management of the relationships with and between students ( Pinnelli and Fiorucci, 2015 ; Bicen and Beheshti, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we recognize that the current study is like another one (del Arco et al, 2022) in that it focuses on Web of Science research areas, country/region publications, published journals, and keywords, but we also present dynamic graphs, which provide more feedback on the trends in flipped classroom research, as shown in Figures 2B, 3A, 4, 6. Not only that, but we also propose several research hotspots and future study directions based on the keyword co-occurrence analysis.…”
Section: Comparison With Similar Studiesmentioning
confidence: 98%
“…The search was carried out before the covid pandemic occurred, therefore it will draw the results of the analysis carried out in 2019 and above. Recent research related to flipped classrooms in general in the range of 2007-2021 has been carried out using web of science databases, and recommends qualitative and quantitative research to analyze the potential of flipped classrooms (del Arco, Mercadé-Melé, Ramos-Pla, & Flores-Alarcia, 2022).…”
Section: Introductionmentioning
confidence: 99%